Second-generation long-acting injections anti-psychotics improve executive functions in patients with schizophrenia: a 12-month real-world study. (1st June 2020) - Magliocco, Fabio; de Filippis, Renato; Aloi, Matteo; Staltari, Filippo Antonio; Gaetano, Raffaele; Segura-Garcia, Cristina; De Fazio, Pasquale
Abstract: Background: The main purpose of this study was to assess possible modifications of cognitive performance among schizophrenia patients treated with long-acting injectable antipsychotics (LAIs) of second generation anti-psychotics (SGAs). Our hypothesis is that the shift from the oral formulation to the LAI formulation of SGAs drugs improves the cognitive performance. The secondary objective was to carry out a head to head comparison of two different SGA-LAI treatments [i.e., 1-month Paliperidone Palmitate (PP1M), monthly Aripiprazole (Ari-LAI)] in our study with an independent and real-world setting. Methods: The sample comprised 32 participants who were consecutively recruited over 12 months. Seventeen patients treated with Ari-LAI and 10 treated with PP1M completed psychopathological, neuropsychological and functional assessments. Group differences were explored through chi-squared and t -tests, as appropriate. GLM Repeated Measures were used to study variations of cognitive performance along 12 months and to test differences between drugs. Results: We found an effect of time on the outcomes investigated but this did not depend on the type of LAI used. Conclusions: In comparison with the previous oral treatment with SGAs, patients showed a significant improvement in neurocognitive function after 12 months of treatment with SGA-LAI. Furthermore, there were no differences between the SGA-LAI regimens. Key points: The main purpose of this study was to assess possible modification of cognitive performance of patients with Schizophrenia treated with second generation long-acting injectable antipsychotics (SGA-LAIs). The secondary objective was to carry out a head to head comparison of two different SGA-LAIs: Paliperidone Palmitate 1-Month (PP1M) and Aripiprazole Monthly (Ari-LAI). Patients showed a significant improvement in neurocognitive function after 12 months of treatment with SGA-LAI. There were no differences between the SGA-LAI regimens. From a practical point of view, switching to LAI formulation seems to produce further social and cognitive improvements in patients who had already benefitted from oral SGA therapy.